High-dose atorvastatin after stroke or transient ischemic attack - Amarenco, Pierre; Bogousslavsky, Julien; Callahan, Alfred; Goldstein, Larry B.; Hennerici, Michael G.; Rudolph, Amy E.; Sillesen, Henrik; Simunovic, Lisa; Szarek, Michael; Welch, K. M. A.; Zivin, Justin A. (The New England journal of medicine, 2006)
BACKGROUND: Statins reduce the incidence of strokes among patients at increased risk for cardiovascular disease; whether they reduce the risk of stroke after a recent stroke or transient ischemic attack (TIA) remains to be established. - METHODS: We randomly assigned 4731 patients who had had a stroke or TIA within one to six months before study entry, had low-density lipoprotein (LDL) cholesterol levels of 100 to 190 mg per deciliter (2.6 to 4.9 mmol per liter), and had no known coronary heart disease to double-blind treatment with 80 mg of atorvastatin per day or placebo. The primary end point was a first nonfatal or fatal stroke. - RESULTS: The mean LDL cholesterol level during the trial was 73 mg per deciliter (1.9 mmol per liter) among patients receiving atorvastatin and 129 mg per deciliter (3.3 mmol per liter) among patients receiving placebo. During a median follow-up of 4.9 years, 265 patients (11.2 percent) receiving atorvastatin and 311 patients (13.1 percent) receiving placebo had a fatal or nonfatal stroke (5-year absolute reduction in risk, 2.2 percent; adjusted hazard ratio, 0.84; 95 percent confidence interval, 0.71 to 0.99; P=0.03; unadjusted P=0.05). The atorvastatin group had 218 ischemic strokes and 55 hemorrhagic strokes, whereas the placebo group had 274 ischemic strokes and 33 hemorrhagic strokes. The five-year absolute reduction in the risk of major cardiovascular events was 3.5 percent (hazard ratio, 0.80; 95 percent confidence interval, 0.69 to 0.92; P=0.002). The overall mortality rate was similar, with 216 deaths in the atorvastatin group and 211 deaths in the placebo group (P=0.98), as were the rates of serious adverse events. Elevated liver enzyme values were more common in patients taking atorvastatin. - CONCLUSIONS: In patients with recent stroke or TIA and without known coronary heart disease, 80 mg of atorvastatin per day reduced the overall incidence of strokes and of cardiovascular events, despite a small increase in the incidence of hemorrhagic stroke. (ClinicalTrials.gov number, NCT00147602 [ClinicalTrials.gov].).
The Stroke Prevention by Aggressive Reduction in Cholesterol Levels (SPARCL) Investigators: Pierre Amarenco, Julien Bogousslavsky, Alfred Callahan, Larry B. Goldstein, Michael Hennerici, Amy E. Rudolph, Henrik Sillesen, Lisa Simunovic, Michael Szarek, K.M.A. Welch, Justin A. Zivin
Gesehen am 06.05.2022